OPTIMALISASI PARENTING DALAM MEMBENTUK KARAKTER ANAK USIA DINI DI PAUD AISYIYAH 13 PEKANBARU: Siska Noviana, Nini Aryani, Herwina - Noviana, Siska; Aryani, Nini; herwina, herwina (P3M STKIP 'Aisyiyah Riau, 2024)
The purpose of this study is to determine parenting activities in shaping the character of early childhood in paud aisyiyah 13 Pekanbaru, and to find out the character education of early childhood in paud Aisyiyah 13 Pekanbaru. Data collection research is conducted by conducting observations, interviews, and documentation, and this study uses descriptive qualitative methods, namely explaining and describing data from the results of research that is conducting direct research on parents, children, and teachers as samples in order to get a concrete picture of parenting activities and character education for children. The method used in this research is descriptive method, by collecting data, compiling data, or classifying it, analyzing and interpreting it. The results showed that the parenting given by parents to their children had started well by teaching various kinds of responsibilities, and through good habituation to their children so that children began to get used to it. Parents provide rules that are applied in the family such as tidying up the play equipment after finishing playing, and parents teach independence to the child even though it is not completely done by the child but through these habits the child starts to get used to doing it. When going to hold parenting activities should be held time that does not interfere with the activities of parents of children, so they can attend activities held at school.